The Indonesian Language Ability in Elementary School Teacher Education Students - Sheryl Mutiara Putri (Nusa Putra University, 2024)
This article was written to provide information about the importance of prospective student teachers, especially elementary school teachers, having language skills. A teacher needs to read books that are useful as sources of teaching materials. On the same occasion, teachers also need to make notes regarding the content of the reading and perhaps on other occasions have to write teaching preparations, write reports, and perhaps write papers. Then, in teacher meetings, in class, and on various occasions you need to listen to conversations between other teachers, students, relations, etc. Of course, in certain contexts it is also necessary to convey thoughts, feelings, facts or other things by speaking. So it is clear that students as prospective teachers need to have adequate language skills in their activities as teachers and as members of society. By providing prospective elementary school teachers with the importance of having language skills, it is hoped that they can foster curiosity and responsibility to learn language skills and be able to apply them in everyday life both as part of teacher professionalism and in everyday life. This paper is limited to studying aspects of language skills, not linguistic studies.